2017
DOI: 10.1371/journal.pone.0186149
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes and mutations in patients affected by recurrent pregnancy loss

Abstract: Recurrent pregnancy loss is a frequently occurring human infertility-related disease affecting ~1% of women. It has been estimated that the cause remains unexplained in >50% cases which strongly suggests that genetic factors may contribute towards the phenotype. Concerning its molecular aetiology numerous studies have had limited success in identifying the disease’s genetic causes. This might have been due to the fact that hundreds of genes are involved in each physiological step necessary for guaranteeing rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…In a somewhat similar study, transcriptome analysis compared endometrial tissues from women experiencing recurrent implantation failure to controls (either spontaneously fertile women or women with at least 1 successful implantation via in vitro fertilization) and identified 82 consistently differentially expressed genes (79). Of the 82 genes identified by this study, 13 (or 15.8%) were identified as modulators of decidualization in our screen (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96). These findings are in Dataset S7.…”
Section: Discussionmentioning
confidence: 57%
“…In a somewhat similar study, transcriptome analysis compared endometrial tissues from women experiencing recurrent implantation failure to controls (either spontaneously fertile women or women with at least 1 successful implantation via in vitro fertilization) and identified 82 consistently differentially expressed genes (79). Of the 82 genes identified by this study, 13 (or 15.8%) were identified as modulators of decidualization in our screen (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96). These findings are in Dataset S7.…”
Section: Discussionmentioning
confidence: 57%
“…[ 10 ] A study based on whole genomic sequencing and bioinformatics analysis demonstrated that mutations in MMP9 showed close association with RSA. [ 11 ] MMP2 and MMP9 belong to gelatinases, a subgroup of MMPs, which are involved in various physiological and pathological progresses. [ 12 ] MMP2 is usually secreted by endothelial cells, interstitial cells, macrophages, T cells, eosnophils, and neutrophils, and MMP9 is mainly synthesized and secreted by inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Successful studies have been made by our research group using WES to identified candidate genes of complex diseases and now in pharmacogenetics. [9][10][11][12][13] According to the Naranjo scale, it was estimated for the patient analyzed that the rhabdomyolysis was induced by rosuvastatin (8 points "probable"). 14,15 Considering the timeline of our patient's medication use (Rosuvastatinezetimibe treatment had been established two years prior the reaction), we estimate that exposure to ticagrelor triggered the rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%